Reverse micellar modified mixed anionic and zwitterionic surfactant system for antibiotic extraction - Siti Norazimah, Mohamad-Aziz; Zularisam, A. W.; Mimi Sakinah, A. M. (Elsevier, 2019)
A reverse micellar was modified by combining the anionic AOT and zwitterionic lauryl sulfobetaine surfactant for the extraction of erythromycin was proposed for the first time as a new approach for antibiotic extraction. The stability of the mixed reverse micelle was evaluated in terms of the critical micelle concentration (CMC) using the Wilhelmy Ring method, as well as the thermodynamic properties prior to extraction. The effect of parameters such as AOT concentration, lauryl sulfobetaine fraction and pH of the aqueous phase was investigated during forward extraction. Isopropanol volume percent (%), NaCl concentration, and pH of aqueous phase were investigated during backward extraction. The thermodynamic analysis confirmed the stability of the mixed AOT/lauryl sulfobetaine reverse micelle with a positive synergistic effect. The surface activity was enhanced, by which the CMC of the mixed reverse micelle was significantly lowered, ranging from 0.7 to 5.7 g/L. The overall thermodynamic data comprising ΔGm (between -15.44 to -20.24 kJ/mol), ΔGads (between -27.03 to -28.97 kJ/mol), and ΔGo ex (range between -0.39 to 8.87 kJ/mol) are affirmative that micellization was spontaneous. Erythromycin was also found to be interfacially active at all tested condition. The highest erythromycin solubilisation (94.2%) was achieved, even with low AOT surfactant (60.0 g/L) which reflects the synergy between AOT and lauryl sulfobetaine. In addition, in the absence of isopropanol, erythromycin was found to be successfully recovered during the backward extraction. However, isopropanol is still considered as a recovery booster which enables higher erythromycin recovery.